Conversion of ER, PR, HER2 and Ki-67 and Prognosis in breast cancer metastases to the brain - Jiaxin, Chen; Jinmei, Zhou; Huiqiang, Zhang; Xuexue, Wu; Xiaobo, Wang; Shaohua, Zhang; Yanhong, Tai; Zefei, Jiang; Tao, Wang (Frontiers in Neurology, 2022)
Objective: This study aimed to analyze the expression levels of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER-2), and Ki-67 proliferation index in the brain metastatic lesions and primary lesions in Chinese patients with breast cancer brain metastasis (BCBM) and determine the correlation between their changes and patients’ survival. Methods: A retrospective analysis was performed on patients with BCBM.The clinical characteristic of these patients was collected. The differences in the expression levels of the ER, PR, HER-2 and Ki-67 index between the primary lesions and brain lesions were evaluated, and the association between the differences and survival was analyzed. Results: The conversion rate of anyone receptor (ER, PR, or HER2) between the primary lesions and brain metastatic lesions was 45.0% (18/40), of which the ER inconsistency rate was 25.0%, the PR inconsistency rate was 22.5%, and the HER-2 inconsistency rate was 15.0%, and the receptor conversion resulted in a subtype conversion of 27.5% (11/40). The patients with HER-2 expression discordance between the primary lesions and the brain metastatic lesions had significantly longer survival times (58.9 months vs. 26.4 months, P=0.04) after diagnosis of brain metastases. Conclusion: In this study, 45.0% of breast cancer patients developed biomarker-conversion between the primary lesions and brain metastatic lesions, and the differences in the expression levels of the ER, PR, and HER-2, the change in Ki-67 index between the primary lesions and brain lesions may predict patients’ survival. Keywords: breast cancer; brain metastases; ER; PR; HER-2